2017
DOI: 10.3389/fmicb.2017.01639
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical and Antibacterial Evaluation of St. John's Wort Oil Macerates Used in Kosovar Traditional Medicine

Abstract: Hypericum perforatum L. (Hypericaceae), or St. John's Wort, is a well-known medicinal herb often associated with the treatment of anxiety and depression. Additionally, an oil macerate (Oleum Hyperici) of its flowering aerial parts is widely used in traditional medicine across the Balkans as a topical wound and ulcer salve. Other studies have shown that Oleum Hyperici reduces both wound size and healing time. Of its active constituents, the naphthodianthrone hypericin and phloroglucinol hyperforin are effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 49 publications
2
29
0
2
Order By: Relevance
“…The antimicrobial activity of the carrier oil, however, is reported for the first time in this study. As with this study, P. armeniaca has also previously been reported to display poor antimicrobial activity (>2.00% v/v) against E. coli , P. aeruginosa , S. aureus, and H. perforatum was previously shown to display poor to no antimicrobial activity against S. aureus [15]. However, to the best of our knowledge, the antimicrobial activity of C. officinalis and P. americana carrier oils are reported here for the first time against all 11 pathogens.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The antimicrobial activity of the carrier oil, however, is reported for the first time in this study. As with this study, P. armeniaca has also previously been reported to display poor antimicrobial activity (>2.00% v/v) against E. coli , P. aeruginosa , S. aureus, and H. perforatum was previously shown to display poor to no antimicrobial activity against S. aureus [15]. However, to the best of our knowledge, the antimicrobial activity of C. officinalis and P. americana carrier oils are reported here for the first time against all 11 pathogens.…”
Section: Resultssupporting
confidence: 64%
“…The chemical composition of the essential oils has been previously reported [1] and is included in Table 1. It is known that the chemical composition of essential oils may vary due to differences in chemotype, storage, harvesting, or plant origin [1315]. For example, the sample of Thymus vulgaris from this study has a lower content of thymol (18.9%) than reported in previous studies (44.7-48.9%) [1618] and the Laurus nobilis sample used in this study contains myrcene and chavicol, as opposed to high levels of 1,8-cineole (35.5-42.3%) as previously reported [19, 20].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, UVactivated hypericin exhibits necrotic and apoptotic effects on human keratinocytes and melanocytes [63]. Notably, chemical analysis of the traditional oleum hyperici formulation used throughout the Balkans as a topical therapy revealed the absence of hypericin in the resulting product; this aligned with ethnographic data suggesting frequent users of the oil did not exhibit symptoms of hypericism [54]. …”
Section: St John’s Wort: Hypericum Perforatum L Hypericaceaementioning
confidence: 88%
“…A study on the antibacterial activity of H. perforatum extracts was found to differ substantially based on the extraction method used, with aqueous and organic extracts generally exhibiting more classic antibacterial activity in growth inhibition of pathogens, whereas the oleum hyperici formulation exhibited mild quorum quenching and anti-biofilm properties against Staphylococcus aureus [54]. A study on the efficacy of oleum hyperici on palatal wound healing in rabbits found that the topical oil treatment showed no additional benefit to healing over that of the control (the olive oil base) [55].…”
Section: St John’s Wort: Hypericum Perforatum L Hypericaceaementioning
confidence: 99%
“…First, most natural ingredients are difficult to extract and purify on a large scale ( Bai et al., 2014 ), and extraction costs are a key factor limiting the conversion of ingredients into products. Second, many herbal ingredients only show moderate effects and are unstable under normal conditions, their performance depends on the structure and properties ( Manda et al., 2014 ; Ho et al., 2016 ; Lyles et al., 2017 ). Thus, the molecular structure of some ingredients will be further improved before use, research in this area is under development.…”
Section: The Effects and Problems Of Traditional Asian Herbs In Skin mentioning
confidence: 99%